An investigation into compressive responses of shape memory polymeric cellular lattice structures fabricated by vat polymerization additive manufacturing. (November 2020) - Keshavarzan, M.; Kadkhodaei, M.; Forooghi, F.
Abstract: A combination of additive manufacturing techniques with shape memory materials, so that the shape, property, or functionality of a 3D printed structure can change as a function of time, has recently created new progress in 4D printing. Low-density lattice structures, due to their unique mechanical properties and engineering characteristics, have been candidates for lightweight structures and energy absorbing applications. In the present work, Rhombic and Body-Centered Cubic (BCC) cellular lattice structures, as well as cylindrical bulk samples, were designed and fabricated with Digital Light Process (DLP) by using shape memory resin. The energy absorption of SMP samples was studied in terms of the capabilities of absorption and recovery. In addition, deformation mechanisms of the structures, the influence of strain rate, cyclic behavior and the strain recovery of the structures after each cycle were investigated. All the studies were done in three different cold, warm and hot programming schemes to evaluate the effects of temperature on shape memory effect of the products. Although both structures showed nearly the same strain recovery rates at all conditions, Rhombic structure was found to possess better functional and structural behaviors than BCC lattice in terms of strength, stiffness, and absorption as well as recovery of the induced energy. Graphical abstract: Image 1 Highlights: Compressive responses of two shape memory polymeric structures are studied. Shakedown phenomenon is observed in stress-strain curves under cyclic loadings. The same strain recovery rates but different mechanical responses are seen.